Pengaruh Motivasi, Kepuasan Kerja, Lingkungan Kerja dan Kompensasi Terhadap Turnover Intention - Vincent Andy Darmawan; Astri Ayu Purwati; Yusnita Octafilia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The main purpose of this research is to determine the effect of motivation, job satisfaction, work environment and compensation on turnover intension. Sampel used in this research is 42 employees who work PT Desali Mitra Sejahtera Pekanbaru. Sampling method used is sensus. Methods of data analysis is multiple linear regression with SPSS. Independent variable is motivation, job satisfaction, work environment and compensation. The dependent variable is the turnover intension. This research adduce that motivation, job satisfaction, and compensation has negative effect, which work environment has no effect on turnover intension.